2015
DOI: 10.1109/lwc.2015.2396071
|View full text |Cite
|
Sign up to set email alerts
|

Beamforming Based on Specular Component for Massive MIMO Systems in Ricean Fading

Abstract: This paper is concerned with massive MIMO systems over Ricean fading channels. To reduce the overhead for estimating channel state information (CSI), we investigate transmit/ receive beamforming transmission only based on the specular component and treat the scattered component as interference. For the scenario without co-channel interference, we show that the ergodic achievable rate can remain unchanged when the transmit power is scaled down by the multiplication of the two numbers of antennas at the transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…This means that P = SNR dg N s L/(N r N t ) for a given designed SNR SNR dg . In fact, there exists a power scaling law for mmWave communications which states that the data transmit power P can be scaled down proportionally to 1/(N r N t ) in order to maintain a desirable BER performance [35].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…This means that P = SNR dg N s L/(N r N t ) for a given designed SNR SNR dg . In fact, there exists a power scaling law for mmWave communications which states that the data transmit power P can be scaled down proportionally to 1/(N r N t ) in order to maintain a desirable BER performance [35].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Due to the fact that the channel state information (CSI) needs to be acquired by channel estimation which will be a heavy overhead, a linear transmission only based on the LOS component in Rician fading environment was proposed in [31]- [33], while scattered component is omitted.…”
Section: Introductionmentioning
confidence: 99%
“…However, the channel estimation will result in not only heavy overhead but also pilot contamination in multi-cells, which will become a serious problem [2,8]. For a point to point massive MIMO system in Ricean fading, to reduce the heavy overhead to estimate the CSI, we investigated a scheme with equal gain transmission /equal gain combining (EGT/EGC), which is only based on the line-of-sight (LOS) component (or say specular component) and has low hardware complexity [9]. It was showed that, with this scheme, the ergodic achievable rate can converge to that of the corresponding MRT/MRC based on the perfect CSI as the two numbers of antennas at the transmitter and receiver go to infinity.…”
Section: Introductionmentioning
confidence: 99%